2012
DOI: 10.1002/cctc.201200205
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Study on the Nucleation and Growth of Au on Pd Seeds with a Cubic or Octahedral Shape

Abstract: This article reports a systematic study on the seed‐mediated growth of Pd–Au bimetallic nanocrystals with a variety of controlled morphologies. The key to the success of this synthesis is to manipulate the reaction kinetics by controlling a set of experimental parameters, which include the amount of ascorbic acid used as a reductant, the amount of HAuCl4 as a precursor to elemental Au, the reaction temperature, and the type of seeds employed. Starting from Pd nanocubes of 18 nm in edge length, Pd–Au bimetallic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
32
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 120 publications
1
32
0
1
Order By: Relevance
“…In the following discussion, we refer to them as "Pd cubic seeds" for simplicity. We chose them as seeds for two major reasons: (i) they had a well-defined shape, together with a set of low-index facets on the surface (8,9); and (ii) their side faces are blocked by Br -ions to ensure selective deposition of atoms onto the corner sites during seed-mediated growth (10)(11)(12). These two distinctive features allowed us to easily track the deposition of atoms and their surface diffusion during a growth process by analyzing the shape or morphology of the final product.…”
mentioning
confidence: 99%
“…In the following discussion, we refer to them as "Pd cubic seeds" for simplicity. We chose them as seeds for two major reasons: (i) they had a well-defined shape, together with a set of low-index facets on the surface (8,9); and (ii) their side faces are blocked by Br -ions to ensure selective deposition of atoms onto the corner sites during seed-mediated growth (10)(11)(12). These two distinctive features allowed us to easily track the deposition of atoms and their surface diffusion during a growth process by analyzing the shape or morphology of the final product.…”
mentioning
confidence: 99%
“…Most recently, our group demonstrated that kinetic control is a simple and versatile means for achieving siteselective overgrowth. [7,9] By controlling the rate at which Ag atoms are formed in a solution, for example, we could confine the nucleation and growth of Ag to one, three, or six of the {100} side faces of a Pd cubic seed. [9] As a result, Pd-Ag bimetallic nanocrystals with both Pd and Ag being exposed on the surface were obtained in high yields.…”
mentioning
confidence: 99%
“…[5e, 6,7] Owing to the formation of a core-shell structure, only those atoms situated on the outer surface of such a bimetallic nanocrystal are available for catalyzing chemical reactions. In comparison, it will be a significant advantage to formulate a bimetallic nanocrystal into a core-frame structure, in which the atoms of both the core and frame portions will be accessible to reactants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A good example is the VIP article by Xia et al, which is featured on the cover of this issue. [7] By a seed-mediated growth mechanism, the authors fabricated bimetallic nanocubes with controlled surface morphologies. By measuring the oxidation of ascorbic acid they concluded that the Pd@Au core-shell nanocubes with concave surfaces exhibited higher activity than nanocubes with flat surfaces.…”
mentioning
confidence: 99%